Pengaruh Net Profit Margin, Return on Equity, Return on Asset, dan Earning Per Share terhadap Harga Saham pada PT Bank Central Asia Tbk Periode 2012-2021 - Hasudungan Pangaribuan; Eti Ariyanti; Ana Septia Rahman (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to determine the effect of Net Profit Margin, Return On Equity, Return On Assets, and Earning Per Share on stock prices at PT. Bank Central Asia, Tbk either partially or simultaneously. The method used is the Associative method with a quantitative approach. The sampling technique used is a sample aimed at the financial statements of PT. Bank Central Asia, Tbk for 10 years period 2012-2021. Data analysis used descriptive analysis, classical assumption test, simple linear regression analysis, multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing. Partially, the Net Profit Margin variable has no significant effect on stock prices. This is evidenced by the tcount value of 1.349 with a significance value of 0.235, which means that this figure is greater than the value of the 0.05 significance level (0.235 > 0.05) or (23.5% > 5%). ie tcount (1,349) < ttable (2,447). Partially, the Return On Equity variable has a negative and significant effect on stock prices. This is evidenced by the tcount value of 2.584 with a significance value of 0.049, which means this number is smaller than the value of the significance level of 0.05 (0.049 < 0.05) or (4.9% < 5%), with a comparison namely tcount (2,584) > ttable (2,447) with a negative sign on tcount. Partially, the Return On Assets variable has a negative and significant effect on stock prices. This is evidenced by the tcount value of 2.645 with a significance value of 0.046, which means that this figure is smaller than the value of the significance level of 0.05 (0.046 < 0.05) or (4.6% < 5%). namely tcount (2,645) > ttable (2,447) with a negative sign on tcount. Partially, the Earning Per Share variable has a significant positive effect on stock prices. This is evidenced by the tcount value of 9.901 with a significance value of 0.000, which means that this figure is smaller than the value of the 0.05 significance level (0.000 < 0.05) or (0% < 5%), with a comparison that is tcount (9,901) > ttable (2,447) with a positive sign on tcount. All independent variables in this study, namely NPM, ROE, ROA, and EPS have an effect on stock prices. This is evidenced by the fcount value of 52.234 with a significant value of 0.000, which means the significant value is less than 0.05 (0.000 < 0.05) or (0% < 5%) , with this condition where fcount is greater than ftable ( 52.234 > 4.53).Â